2021
DOI: 10.1002/cbdv.202100117
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, Antibacterial Evaluation and Molecular Docking Studies of Some Newer Baenzothiazole Containing Aryl and Alkaryl Hydrazides

Abstract: The alarming rise of bacterial resistance is occurring worldwide and endangering the efficacy of antibiotics. Therefore, development of new and efficient antibacterial agents remains paramount. In the present work, we designed and synthesized a series of N′‐(1,3‐benzothiazol‐2‐yl)‐substituted aryl/aralkyl hydrazides C1–C27 and evaluated them in vitro for their antibacterial activity. Among all tested compounds, C10, C15, and C24 showed potent activity against Staphylococcus aureus ATCC 43300 (MRSA). Minimum ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…In 2021, Gurram et al 81 reported 27 novel benzothiazoles with antibacterial activity, among which compounds 16a−e exhibited good antibacterial activity against MRSA after the primary screening (Figure 17). The SARs revealed that benzothiazole compounds whose substituents had strong electronegative groups at the C-2 or C-4 positions and electron-withdrawing groups (EWGs) at the C-3 or C-5 positions of benzene all had strong anti-MRSA activity.…”
Section: -Aminobenzothiazolesmentioning
confidence: 99%
“…In 2021, Gurram et al 81 reported 27 novel benzothiazoles with antibacterial activity, among which compounds 16a−e exhibited good antibacterial activity against MRSA after the primary screening (Figure 17). The SARs revealed that benzothiazole compounds whose substituents had strong electronegative groups at the C-2 or C-4 positions and electron-withdrawing groups (EWGs) at the C-3 or C-5 positions of benzene all had strong anti-MRSA activity.…”
Section: -Aminobenzothiazolesmentioning
confidence: 99%